Формирование младшего офицерского звена российской армии во второй половине ХІХ - начале ХХ столетия - Стоян, Т.А. (Культура народов Причерноморья, 2005)
В статье раскрываются особенности пополнения младшего офицерского звена вооруженных сил Российской империи во второй половине ХІХ - начале ХХ столетия. Показано, что на качественный состав младшего командного звена российской армии значительное влияние оказывали не только уровень подготовки в военно-учебных заведениях, но и условия службы обер-офицеров, в первую очередь - чинопроизводство. При написании статьи использованы проблемно-хронологический, сравнительно-исторический и статистико-аналитический методы исследования. Peculiarities of reinforcement of the second officer team of Russian army at the second half of the 19th - at the beginning of the 20th century are being disclosed in the article. It have been shown there that the staff quality of the second officer team of Russian army depended not only on the level of training at the military educational institutions but also on the special service conditions of the second team officers, first of all on the giving of ranks. . Problem-chronological, comparative-historical, statistical-analytical methods of research have been used.